Меню

УСЛОВИЕ:
Решить неравенства a) \( 2^{x} < \frac{1}{2} \)
b) \( 3^{2x-1} -3^{2x-3} < \frac{8}{3}\)
c) \( 17 \frac{x}{y-8} \geq 17 \)
d) \( log_{ 0.2} x < 3 \)
e) \( log_{ 0.3} ( x^{2} +22) < log_{0.3} 13x \)
Возвести в степень
a) \( (\frac{18a ^{9}l ^{3} c ^{8} }{3 x^{4} b ^{4}c ^{4} } ) ^{-3} \)
b) \(( \frac{7a ^{15}b ^{19}c ^{-24} }{21a ^{1}b ^{-2}c ^{4} } ) ^{ \frac{2}{7} } \)
Вычислить
a) $$ \sqrt{x81} * \sqrt{4} + \sqrt{4} \sqrt[3]{343} $$
b) $$ \sqrt{9+6*1+1} $$
Упростить выражение
a) sin(n+t)
b) \( cos(90^{0} + t)\)
c) \(tg (\frac{3 \pi }{2} -t ) \)
d) \( ctg (360^{0} -t ) \)
Найти основной период функции y=cos 3x
Найти значение функций
\( y=2sin(x- \frac{ \pi }{6} ) +1 \) при \( x=\frac{4 \pi }{3} \)
\( y=cosx x^{2} при x=\pi \)


РЕШЕНИЕ:$$ a) 2^x < \frac{1}2\\ 2^x < 2^{-1}\\ x < -1 \\ b) 3^{2x-1}-3^{2x-3} < \frac{8}3\\ 3^{2x}*3^{-1}-3^{2x}*3^{-3} < \frac{8}3\\ t=3^{2x}\\ \frac{1}{3}t-\frac{1}{27}t < \frac{8}{3} \\ \frac{8}{27}t < \frac{8}{3}\\ t < 9\\ 3^{2x} < 9\\ 3^{2x} < 3^2\\ 2x < 2\\ x < 1 $$
$$ c) 17^{\frac{x}{y-8}}\geq17\\ \frac{x}{y-8}\geq1\\ x\geq y-8 \\ d) log_{0,2}x < 3\\ \frac{log_3x}{log_30,2} < log_327\\ log_3x < log_327*log_30,2\\ log_3x < log_3(27*log_30,2)\\ x < 27log_30,2 \\ e) log_{0,3}(x^2+22) < log_{0,2}13x\\ x^2+22 > 13x\\ x^2-13x+22 > 0\\ x^2-13x+22=0\\ D=(-13)^2-4*1*22=81=9^2\\ x_1=\frac{13+9}{2}=11; \\ x_2=\frac{13-9}{2}=2\\ x\in(-\infty;2)\cup(11;\infty) $$

$$ a) (\frac{18a^9l^3c^8}{3x^4b^4c^4})^{-3}=\\ =\frac{18^{-3}a^{9*(-3)}l^{3*(-3)}c^{4*(-3)}}{3^{-3}x^{4*(-3)}b^{4*(-3)}}= \\ =\frac{18^{-3}a^{-27}l^{-9}c^{-12}}{3^{-3}x^{-12}b^{-12}}=\\ =\frac{27(xb)^{12}}{18^3(a^9l^3c^4)^3} \\ b) (\frac{7a^{15}b^{19}c^{-24}}{21a^1b^{-2}c^4})^{\frac{2}7}=\\ =(\frac{a^{14}b^{21}c^{-28}}{3})^{\frac{2}7}=\\=3^{-\frac{2}7}a^4b^6c^{-8} $$

$$ a) \sqrt{x81}*\sqrt{4}+\sqrt{4}\sqrt[3]{343}=9\sqrt{x}*2+2*7=14+18\sqrt{x}\\ b) \sqrt{9+6*1+1}=\sqrt{16}=4 \\b) cos(90^0+t)=-sint \\ c) tg(\frac{3}2\pi-t)=ctgt \\ d) ctg (360^0-t)=-ctgt $$


y=cos(3x)
Период функции y=cos(x) T=2π
cos(x)=cos(x+T)
cos(3x)=cos(3(x+K))
3(x+K)=2π
3x+3K=2π
x=2/3π

$$ y=2sin(x-\frac{\pi}{6})+1; \\ x=\frac{4\pi}3\\ y=2sin(\frac{4\pi}3-\frac{\pi}{6})+1=2sin(\frac{14\pi}{12})+1=\\=2sin(\frac{\pi}{6})+1=2*0,5+1=2\\ y=cos(x^2); \\ x=\pi\\ y=cos(\pi^2)=-0,903 $$




Похожие примеры: